2000
DOI: 10.2134/agronj2000.92124x
|View full text |Cite
|
Sign up to set email alerts
|

Binary Legume–Grass Mixtures Improve Forage Yield, Quality, and Seasonal Distribution

Abstract: Yield and forage quality of kura clover (Trifolium ambiguum Bieb.) and intermediate wheatgrass [Thinopyrum intermedium (Host.) Barkw. & D.R. Dewey] mixtures compared with commonly grown forages such as alfalfa (Medicago sativa L.) and smooth bromegrass (Bromus inermis Leyss.) have not been fully explored. Our objective was to evaluate the effects of alfalfa, birdsfoot trefoil (Lotus corniculatus L.), and kura clover grown in binary mixtures with orchardgrass (Dactylis glomerata L.), smooth bromegrass, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
238
9
22

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(299 citation statements)
references
References 13 publications
30
238
9
22
Order By: Relevance
“…Quando necessário, antes da ANOVA, os dados foram transformados com a função arco-seno, para satisfazer os testes de normalidade (Dagnelie, 1986 A pastagem pura de azevém anual apresentou teor médio de PB de 122,6±45,26 g kg -1 , enquanto a pastagem consorciada apresentou teores significativamente mais elevados (163,3±49,01 g kg -1 ), apesar da baixa proporção de trevos (6,2%). Resultados semelhantes foram obtidos por Sleugh et al (2000), ao verificar teores de PB em pastagens de gramíneas inferiores ao observado em misturas de leguminosas e gramíneas. Diversos autores (Zemenchik et al, 2002;Deak et al, 2007) têm relatado que a variação na concentração de PB, em pastagens com misturas de espécies forrageiras, é explicada pela proporção de leguminosas.…”
Section: Methodsunclassified
See 2 more Smart Citations
“…Quando necessário, antes da ANOVA, os dados foram transformados com a função arco-seno, para satisfazer os testes de normalidade (Dagnelie, 1986 A pastagem pura de azevém anual apresentou teor médio de PB de 122,6±45,26 g kg -1 , enquanto a pastagem consorciada apresentou teores significativamente mais elevados (163,3±49,01 g kg -1 ), apesar da baixa proporção de trevos (6,2%). Resultados semelhantes foram obtidos por Sleugh et al (2000), ao verificar teores de PB em pastagens de gramíneas inferiores ao observado em misturas de leguminosas e gramíneas. Diversos autores (Zemenchik et al, 2002;Deak et al, 2007) têm relatado que a variação na concentração de PB, em pastagens com misturas de espécies forrageiras, é explicada pela proporção de leguminosas.…”
Section: Methodsunclassified
“…Contudo, para que esses sistemas expressem todo o seu potencial, algumas práticas devem ser consideradas, como rotação de culturas, plantio direto, correção da acidez e da fertilidade do solo, emprego de genótipos melhorados e manejo correto da pastagem, com carga animal adequada (Moraes et al, 2002). Smith et al (2008) relatam que a crescente diversidade de espécies nos sistemas de produção pode levar a aumentos significativos na produção das culturas, especificamente na do milho. Sleugh et al (2000) sugerem que o maior nível de proteína bruta, em pastagens constituídas por misturas de leguminosas e gramíneas, contribui para a redução da necessidade de fornecimento de suplementação alimentar para a produção animal.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Davidson & Robson (1990) reported that ryegrass in a grass-clover mixture consistently had higher N contents than pure grass grown in monoculture. Thirdly, legumes improve seasonal distribution of the forage by reaching its peak production at a later stage (spring) in the year compared to the companion ryegrass crop (Sleugh et at., 2000). The only disadvantages of legumes in a pasture are the possibility of bloat in animals and the poor predictability of legume perfonnance (Miles & Manson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in clover content as a result of such fertiliser N applications are however a reason for concern, as clover is instrumental in ensuring that fodder of acceptable quality is produced (Sleugh, Moore, George & Brummer, 2000). A clover content of between 30 and 50 percent, on a dry mass base, j is required to ensure the production of forage of acceptable quality and quantity (Martin, 1960;Curll, 1982;Pflimlin, 1993 cited by Schils, Vellinga & Kraak, 1999;Harris, 1994).…”
Section: Introductionmentioning
confidence: 99%